A historian woman between the living and the dead; between the North and the South (Tempo e Argumento, 2024)
The Battle of Algiers, more accurately referred to by historians as “the great repression of Algiers” (Gilbert Meynier), has become a landmark event, symbolizing, for a part of the world, the Algerian War of Independence. Along with my colleague Fabrice Riceputi, I conduct a collaborative historical project on forced disappearances during the Battle of Algiers. On the project’s website, we have created a page for each identified abductee and issued a call for families to confirm the fate of everyone. Since then, we have been contacted by dozens of families: sometimes they send us a person's photos, provide written testimonies, or send us documents they have kept. In our investigations as historians of the present time, we take on roles that are not always inherent to our subject. To put it another way, we push the boundaries of our field, navigating between the living and the dead. This is the focus of this article.
Keywords: Battle of Algiers; enforced disappearances; memory politics